Morphological characteristics and phylogenetic analyses revealed four new species of Agaricales from China - Xu, Jize; Jiang, Yi; Wang, Tiantian; Zhang, Di; Li, Xiaobin; Hosen, Md. Iqbal (Frontiers in Microbiology, 2023)
Four new species viz. Hohenbuehelia tomentosa, Rhodophana qinghaiensis, Rhodophana aershanensis, and Spodocybe tomentosum are described from China based on their unique morphological features and molecular evidence. The Hohenbuehelia tomentosa is mainly characterized by its dark brown pileus with finely dense pure white tomentum, dirty white, decurrent lamellae, eccentric stipe, smooth spores and fusiform metuloid cystidia. The characteristics of Rhodophana qinghaiensis are glabrous, smooth and reddish-brown pileus, gray-orange lamellae and initially light orange, becoming reddish brown stipe. The unique morphological characteristics of Rhodophana aershanensis are reddish brown pileus with age, brown-orange towards margin, light orange lamellae and stipe dark brown at first, reddish-brown with age. Spodocybe tomentosum is characterized by subclitocyboid and small basidiomes, finely dense pure white tomentum on the pileus surface, and broadly ellipsoid to ellipsoid and smaller basidiospores. Phylogenetic analysis showed that Hohenbuehelia tomentosa, Rhodophana qinghaiensis, Rhodophana aershanensis and Spodocybe tomentosum formed an independent lineage, respectively. Full descriptions, illustrations and phylogenetic trees of the four new species are provided in this study.